A CALORIMETRIC STUDY OF SOME METAL-ION COMPLEXING EQUILIBRIA - (:unkn) unknown (ELSEVIER SCIENCE BV, 1992)
The cumulative enthalpies of formation of Sc(III)-F- and Ag(I)-NH3 complexes were determined using a conventional isothermally-jacketed solution calorimeter with a solid gold inner can. The stepwise enthalpies of formation of ScFn(3-n)+ (n = 1-4) from HF(aq) in 0.5 M (Na+,H+)ClO4- at 25-degrees-C are -2.156 +/- 0.402, -4.413 +/- 1.081, -3.467 +/- 1.190, and -11.880 +/- 0.977 kcal mol-1, respectively. The entropy of formation of the ScF2+ complex is + 29.0 cal degrees-C-l mol-1. Correcting this value for the substitution of a fluoride ion for a coordinated water molecule gives an entropy change of + 14.18 cal-degrees-C-1 mol-1 and shows the expected trend of the dependence of the entropy change on ionic radius when it is compared to corrected values of DELTA-S kelvin for the formation of AlF2+, FeF2+ and InF2+ from the metal 3+ ion and aqueous fluoride ion in 0.5 M ClO4-. The cumulative enthalpies of formation of Ag(NH3)+ and Ag(NH3)2+ are -5.134 +/- 0.492 and - 13.536 +/- 0.137 kcal mol-1, respectively, in 1 M NH4NO3(aq) at 25-degrees-C. The associated cumulative entropy changes are -2.07 +/- 1.68 and -12.58 +/- 0.470 cal degrees-C-1 mol-1 and correspond to the sum of the changes for removing a coordinated water molecule in each step and coordinating an ammonia molecule in its place, plus the statistical entropy change for coordinating an ammonia molecule in the two available positions in the coordination sphere of the Ag(I) ion.